An exploratory study of the influence of an absent father on the identity formation of women - Varney-Wong, Anna (Department of Social Development, 2020)
This clinical study explored the significance of the experience of an absent father on the identity formation of women in an attempt to understand the psychological effect of father absence and the role this experience plays in terms of the daughter's, confidence, self esteem, social identity and intimate relationships. The influence on resiliency of the absent father experience is also a critical aspect of this research. The two theoretical frameworks that guide this clinical study are: the psychodynamic approach, more specifically, objects relations, and self psychology, and Bowens’ family systems theory. The research method is a qualitative design to develop an in-depth understanding of the sample population of twenty adult women who had grown up without a father and live in the geographical area of Cape Town. Data was collected using an in-depth, semistructured interview, facilitated by open-ended questions contained in an interview guide. A wide range of conditions affected participants in the study. Presence of a positive caregiver experience in early childhood appeared to play a role in the psychological well-being of the women. The quality of the women's relationships also appeared to be influenced by their early relational experiences. Poverty was the cause of hardship for many of the participants. Some of the women experienced shame and an internal poverty of worthlessness resulting from perceived rejection and abandonment by their fathers. These psychological experiences were found to influence social interactions and they were often less socially engaged than their peers. The women were generally resilient, at least to some degree and received a measure of support from others, however many felt they were their own most reliable resource.